Nothing like it in the world : the men who built the transcontinental railroad, 1863-1869 - Ambrose, Stephen E. (Simon & Schuster, 2000)
Profiles the men who built the transcontinental railroad, the investors who risked their businesses to fund it, the politicians who understood its importance, the Irish and Chinese immigrants who worked on it, and the other laborers who did the dangerous work of laying the track.